The MET Oncogene as a Therapeutical Target in Cancer Invasive Growth - Luraghi, Paolo; Schelter, Florian; Krüger, Achim; Boccaccio, Carla (Frontiers in Pharmacology, 2012)
The MET proto-oncogene, encoding the tyrosine kinase receptor for Hepatocyte Growth Factor (HGF) regulates invasive growth, a genetic program that associates control of cell proliferation with invasion of the extracellular matrix and protection from apoptosis. Physiologically, invasive growth takes place during embryonic development, and, in post-natal life, in wound healing and regeneration of several tissues. The MET oncogene is overexpressed and/or genetically mutated in many tumors, thereby sustaining pathological invasive growth, a prerequisite for metastasis. MET is the subject of intense research as a target for small-molecule kinase inhibitors and, together with its ligand HGF, for inhibitory antibodies. The tight interplay of MET with the protease network has unveiled mechanisms to be exploited to achieve effective inhibition of invasive growth.